(untitled) (San Francisco, 1997)
A book to visit occasionally for something new to stretch our understanding, to think about, and to integrate into our work.... This is a treasure-trove of some of the best thinking today on leadership, management, and strategy. If we use it as a self-paced seminar on how to advise, create, and lead the organizations of our future, we will be better equipped by far than most of our competitors." -Journal of Management Consulting
Keywords: Thay đổi tổ chức,Organizational change